Pulmonary Sequestration Second case series from Iraq - hussen, waleed M. (Journal of the Faculty of Medicine Baghdad, 2021)
Background:Pulmonary sequestration is a lung tissue (out of function), that received its blood supply from anomalous artery and not continuous with the tracheobronchial tree.Aim:To report a personal experience in dealing with five patients with pulmonary sequestration, due to anomalous arterial supply from the descending Thoracic Aorta ,ways of diagnosis and proper surgical management.Patients and Methods:Five patients with pulmonary sequestration, admitted, investigated and surgically managed at the department of Thoracic and Vascular surgery, in the surgical sub specialties hospital of the Medical City Teaching Complex during ten years period (2010-2019).Results :Four of our patients were male, the remaining one was a female, all managed successfully byOperative ligation of the anomalous blood supply and resection of the involved segment or lobe.Conclusion:Resection of the involved segment or lobe after ligation of the anomalous artery offers the best chance of cure.